Analysis of the disposal of sanitary sewage in a riverside area in northern Brazil (Research, Society and Development, 2020)
Adequate targeting of sanitary sewage is essential for improving the population's quality of life and protecting the environment. In this context, the research aimed to identify how to dispose of sanitary sewage on Mamangal Island, municipality of Igarapé-Miri, Pará. For this purpose, a study was carried out to characterize the island's sanitation in addition to the investigation of basic sanitation conditions. in 215 households distributed among the five local communities, in order to know the profile of the residents and the sanitation conditions, in addition to observations of the area. As a result, it was found that 89% of the residents disposed of waste directly in the yard / at the back of the house / undergrowth, noting the lack of basic sanitation. All respondents said they recognized the sanitation problems and their impacts on health, however, they were in a situation of socio-environmental vulnerability. Thus, it is necessary to implement basic sanitation infrastructure, which can offer dignity and quality of life to that population, as recommended by Law No. 11455 (2007).